Case report: Hydrometrocolpos conditioning recurrent urinary tract infections - Malanowska, Ewelina; Krzyścin, Mariola; Sowińska-Przepiera, Elzbieta; Starczewski, Andrzej; Sulikowski, Tadeusz; Balzarro, Matteo; Rubilotta, Emanuele (Frontiers in Surgery, 2022)
We present a case of a 12.5-year-old girl who has suffered from recurrent urinary tract infections for many years but has never undergone a detailed diagnostic process. Only as a teenager did she complain of acute pain in her lower abdomen and it turned out that her genital organs had not properly developed. She had an obstructive defect in the reproductive tract. When there was a significant amount of discharge collected in the lumen of the genital tract and the organs had distended, acute pain appeared, which allowed us to make the diagnosis. In the diagnostic process, transperineal ultrasonography turned out to be extremely helpful, allowing us to establish the type and thickness of the obstruction. The patient underwent excision of transverse vaginal septum, and postoperative silicon dilators were used to prevent the recurrence of the obstruction. There was no recurrence of urinary infection or complications during the 11 months of follow-up.